2010
DOI: 10.1111/j.1750-3841.2010.01859.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Sprays of Food‐Grade Acids and Plant Extracts are More Effective than Conventional Sprays in Decontaminating Salmonella Typhimurium on Spinach

Abstract: About 40000 people fall victim to Salmonella infections every year in the United States. Recent occurrences of Salmonella contaminated spinach and its recalls have accelerated the need for efficient antimicrobials targeting these pathogens. Our study was aimed at evaluating the inhibitory properties of malic, tartaric, and lactic acids, and grape seed extract (GSE) alone and in combinations and their application methods against Salmonella Typhimurium-inoculated spinach using a response surface method. Fresh sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 22 publications
3
28
0
Order By: Relevance
“…Similarly, Lin et al (2002) obtained a 4 log CFU/g reduction of Salmonella Enteritidis on lettuce with application of 1.5% lactic acid at room temperature, but severe browning of the lettuce occurred with this treatment. Ganesh et al (2010) also found that 2% lactic acid when sprayed on inoculated spinach leaves reduced S. Typhimurium by approximately 1.5 log CFU/g during refrigerated storage as compared to the control.…”
Section: Sanitizer Effect On Salmonellamentioning
confidence: 92%
“…Similarly, Lin et al (2002) obtained a 4 log CFU/g reduction of Salmonella Enteritidis on lettuce with application of 1.5% lactic acid at room temperature, but severe browning of the lettuce occurred with this treatment. Ganesh et al (2010) also found that 2% lactic acid when sprayed on inoculated spinach leaves reduced S. Typhimurium by approximately 1.5 log CFU/g during refrigerated storage as compared to the control.…”
Section: Sanitizer Effect On Salmonellamentioning
confidence: 92%
“…Among the six compounds identified, the literature has already demonstrated the antimicrobial activity of three of them (malic acid, scopoletin and ferulic acid) [Craveiro and Silveira, 1982;Ganesh et al, 2010;Borges et al, 2012]. The antimicrobial activity of the three other compounds has yet to be uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…Electrostatic spray application demonstrated successful results in reducing foodborne pathogens on various food applications such as chicken carcasses, eggs, and bananas (Kim et al, 2005;Law & Cooper, 2001;Russell, 2003a,b). Ganesh et al (2010) reported that electrostatic spraying (in comparison to conventional treatments) of spinach with malic acid (MA) and GSE yielded 2.6 and 3.3 log reductions of L. monocytogenes and Salmonella Typhimurium (S.T) on days 7 and 14 respectively compared to the reductions by control (0.1 and 0.0 log CFU/g) ( Table 3). Combination of an electrostatic spray of 2% tartaric acid and 2% GSE, and a spray of 2% MA and 2% GSE led to more reductions in bacterial log numbers: 3.3 to 3.6 log CFU/g and 1.5 to 3.8 logs CFU/g respectively (Ganesh et al, 2010).…”
Section: Use Of Electrostatic Spray In Delivering Antimicrobialsmentioning
confidence: 98%
“…Ganesh et al (2010) reported that electrostatic spraying (in comparison to conventional treatments) of spinach with malic acid (MA) and GSE yielded 2.6 and 3.3 log reductions of L. monocytogenes and Salmonella Typhimurium (S.T) on days 7 and 14 respectively compared to the reductions by control (0.1 and 0.0 log CFU/g) ( Table 3). Combination of an electrostatic spray of 2% tartaric acid and 2% GSE, and a spray of 2% MA and 2% GSE led to more reductions in bacterial log numbers: 3.3 to 3.6 log CFU/g and 1.5 to 3.8 logs CFU/g respectively (Ganesh et al, 2010). An advantage of electrostatic spraying over conventional spraying is that electrostatic spraying can cause a consistently even and retained surface coverage with the applied antimicrobial.…”
Section: Use Of Electrostatic Spray In Delivering Antimicrobialsmentioning
confidence: 98%
See 1 more Smart Citation